Future Emergencies: Temporal Politics in Law and Economy. (March 2015) - Opitz, Sven; Tellmann, Ute
This article develops a notion of the 'politics of time' in order to analyse the effects that imaginations of future emergencies have in the fields of law and economy. Building on Niklas Luhmann's theory of social time, it focuses on the multiplex temporalities in contemporary society, which are shown to interact differently with the 'emergency imaginary'. We demonstrate that the apprehension of the future in terms of sudden, unpredictable and potentially catastrophic events reinforces current modes of producing financial futurity, while it undermines the procedural rhythm and retroactive sentencing of liberal law. As a whole, the article supplements the analysis of the 'politics of truth' prevalent in the current debate about precaution and pre-emption with a theoretical perspective on social temporality.